Digital Leadership, Work-Life Balance, Compensation, Job Satisfaction, and Employee Engagement - Gede Sri Darma; I Nyoman Sulistiana (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the relationship between digital leadership, work-life balance, compensation, and job satisfaction on employee engagement due to quiet quitting phenomenon of Rural Bank’s employees in Denpasar who were affected by Covid-19 Pandemic. The population was 519 employees, with the proportionate stratified random sampling method, the questionnaire was filled in by 207 respondents. Data processing was carried out using Smart PLS 4. The results showed that digital leadership, work-life balance, and compensation had a positive and significant effect on job satisfaction; then digital leadership, work-life balance, and job satisfaction have a positive and significant effect on employee engagement; but compensation has no effect on employee engagement. Compensation does not guarantee employee engagement to the company. An interesting finding in this study is the dominant factor influencing employee engagement is digital leadership, followed by work-life balance, and finally compensation. Theoretically, this study contributes to the knowledge that to prevent quiet quitting, the most important aspect that can be the answer is enhance digital leadership.